Trypsin Digestion Pretreatment of Kelp Samples and the Iodine Speciation Analysis of Iodate, Iodide, MIT, and DIT by HPLC-ICP-MS - Tong Chen; Wanjing Cui; Ziwei Bi; Yafei Guo; Guoliang Zhu; Xiuyun Pan; Zhiqiang Cui; Zhen Yang; Tianlong Deng (Journal of Chemistry)
The analysis of iodine content in kelp is mainly focused on determining total iodine content, which lacks a rapid and sensitive analytical method for iodine species corresponding to iodate, iodide, monoiodotyrosine (MIT), and diiodo-tyrosine (DIT). Based on exploring the pretreatment methods of enzymatic hydrolysis of kelp, a rapid determination method of high-performance liquid chromatography and inductively coupled plasma mass spectrometry (HPLC-ICP-MS) for different iodine species existed in kelp samples was established. The pretreatment method is trypsin hydrolysis of kelp samples treated at 50°C for 10 hours, then the extraction solution was obtained by centrifugation, and filtration was proved for the first time. A high-efficiency separation anion-exchange column (Dionex IonPac AS-14) for iodate, iodide, MIT, and DIT with 0.1 mol·L−1(NH4)2CO3 solution at pH = 9 as a mobile phase, a flow rate of 0.8 mL·min−1 for the first 1500 s, and 1.2 mL·min−1 for the last 1800 s was confirmed. The linear ranges of the standard calibrations on four iodine species are 1.0–150 μg·L−1, and the detection limits are 1.62, 1.02, 1.59, and 2.55 μg·L−1, respectively, while the RSD values of four iodine species are all less than 2%. Under the optimized conditions, the proposed method was successfully applied for the speciation analysis of iodine in kelp samples.